Strategi Komunikasi Pemasaran Dalam Meningkatkan Brand Awareness Pada Forthis House - Wardani, Anna; Boer, Kheyene Molekandella (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to determine the effectiveness of marketing communication in influencing consumer behavior, particularly in encouraging purchasing decisions. The research method used in this study is a qualitative descriptive approach, which seeks to provide an in-depth description of marketing communication strategies in increasing brand awareness among Forthis House customers. The data used in this research consists of primary and secondary data. Primary data were obtained through direct observation and in-depth interviews with key informants, namely the owner of Forthis House and two regular customers selected through purposive sampling until data saturation was reached. Meanwhile, secondary data were collected from various written sources such as books, journals, and relevant documents to support field findings. Data collection techniques included non-participatory observation, in-depth interviews, and documentation in the form of photos or supporting archives. Data analysis was carried out using the Miles, Huberman, and Saldana model, which consists of three stages: data condensation, data display, and conclusion drawing. Through this approach, the research is expected to provide a comprehensive, valid, and meaningful overview of Forthis House's marketing communication strategies in increasing brand awareness. The results of the study indicate that the marketing communication strategy implemented by Forthis House Samarinda has proven effective in enhancing brand awareness and driving sales growth. The implementation of various promotional mix elements such as advertising through billboards and social media, interactive sales promotions, and a friendly and targeted personal selling approach has successfully built a strong relationship between the brand and its consumers. Forthis House’s responsiveness to customer feedback also contributes to product innovation and service improvement, thereby strengthening customer loyalty. In addition, the use of visual content on digital platforms not only attracts attention but also builds strong emotional engagement with the audience, especially the younger generation. Overall, this integrated marketing communication strategy has effectively reinforced brand image, increased customer loyalty, and positioned Forthis House as one of the competitive brands in Samarinda’s culinary market.